PENGARUH PEMBERIAN KOMPRES BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ASUHAN KEPERAWATAN AN. M DENGAN DIAGNOSA MEDIS FEBRIS TYPHOID DI RS WIJAYA KUSUMA PURWOKERTO - Nur Arifin; Indri Heri Susanti (JURNAL PENGABDIAN MANDIRI, 2022)
Typhoid fever is an infection that has a sudden or acute nature usually in the digestive tract, there are initial symptoms, namely digestive disturbances and consciousness, fever for more than one week (Maghfiroh & Siwiendrayanti, 2016). Infectious diseases occur due to the entry of microorganisms in the form of viruses, bacteria and fungi that can cause coughs, runny noses, sore throats, upper respiratory tract infections (ARI) and pneumonia. Infectious diseases are characterized by the occurrence of fever (Pratiwi et al., 2021). Fever is an increase in body temperature of 1oC or greater above the average value of normal temperature where normal body temperature ranges from 35.5 – 37.5 oC oral temperature, 34.7 – 37.3 oC axillary temperature and 36.6-37.9 oC rectal temperature (Potter & Perry, 2015). The United Nations International Children's Emergency Fund (UNICEF) estimates that approximately 12 million children die each year, one of which is caused by fever (Arifuddin, 2016). The incidence of fever in the world is estimated to reach 4-5% of the total population in the United States, South America, and Western Europe. The incidence of fever in Asia is higher, such as in Japan reporting the incidence of fever between 6-9% incidence of fever, in India it is 5-10% and in Guam is 14% (Francis et al., 2016). Based on the research of Pathak et al., (2020) it is known that the incidence of fever in children with infectious diseases in India is 47%. The number of fever sufferers in Indonesia is reported to have a higher incidence compared to other countries, namely around 80-90% of all reported fevers are simple fevers (Kemenkes RI, 2017).